2014
DOI: 10.1063/1.4873540
|View full text |Cite
|
Sign up to set email alerts
|

Detection of terahertz radiation by tightly concatenated InGaAs field-effect transistors integrated on a single chip

Abstract: A tightly concatenated chain of InGaAs field-effect transistors with an asymmetric T-gate in each transistor demonstrates strong terahertz photovoltaic response without using supplementary antenna elements. We obtain the responsivity above 1000 V/W and up to 2000 V/W for unbiased and drain-biased transistors in the chain, respectively, with the noise equivalent power below 10−11 W/Hz0.5 in the unbiased mode of the detector operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…7), we used the following parameters for AlGaN/GaN HFET L = 0.25 m, The values of NEP presented in [21] for InGaAs FETs (NEP ~ 8•10 -12 W/Hz 1/2 ) seems as overestimated ones as for V sig and NEP calculations the effective antenna area was taken a physical area of the structure with the chain of four FETs only (without area of the contacts), which is several times lower than the effective area of the antenna  2 /4 [16,19] that was taken in this article as a normalization constant.…”
Section: Results Of the Measurementsmentioning
confidence: 99%
“…7), we used the following parameters for AlGaN/GaN HFET L = 0.25 m, The values of NEP presented in [21] for InGaAs FETs (NEP ~ 8•10 -12 W/Hz 1/2 ) seems as overestimated ones as for V sig and NEP calculations the effective antenna area was taken a physical area of the structure with the chain of four FETs only (without area of the contacts), which is several times lower than the effective area of the antenna  2 /4 [16,19] that was taken in this article as a normalization constant.…”
Section: Results Of the Measurementsmentioning
confidence: 99%
“…It is shown that such HEMT chain exhibits strong THz photovoltaic response due to asymmetric form of the T-gate in each HEMT in the chain. We obtained the voltage responsivity above 1 kV/W in the unbiased mode of the detector operation [7].…”
Section: Hemtsmentioning
confidence: 99%
“…Detection and generation of terahertz (THz) radiation based on excitation of plasma wave oscillations in the two-dimensional electron gas (2DEG) channel of field-effect transistor (FET)-like structures were theoretically predicted by M. Dyakonov and M. Shur [1]. In recent years the achieved responsivity and noise equivalent power (NEP) of such detectors have approached the values meeting the demands of practical applications [2][3][4][5][6][7]. Main designs of plasma wave THz detectors include single transistors with the antenna [3,4,7], single transistors with grating/interdigitated gate [2,8,9] and several transistors connected by external wires or integrated on a chip [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years the achieved responsivity and noise equivalent power (NEP) of such detectors have approached the values meeting the demands of practical applications [2][3][4][5][6][7]. Main designs of plasma wave THz detectors include single transistors with the antenna [3,4,7], single transistors with grating/interdigitated gate [2,8,9] and several transistors connected by external wires or integrated on a chip [5,6]. Lateral dimensions of most highly sensitive detectors are much smaller than the half-wavelength of THz radiation [5,6] and in an experiment one usually deals with a single detector surrounded by wiring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation